The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0100-40422008000400005
|View full text |Cite
|
Sign up to set email alerts
|

Piranoflavonas inéditas e atividades tripanocidas das substâncias isoladas de conchocarpus heterophyllus

Abstract: . do Café, s/n, 14040-903 Ribeirão Preto -SP, BrasilRecebido em 18/5/07; aceito em 14/11/07; publicado na web em 19/3/08 NEW PYRANOFLAVONES AND TRYPANOCIDAL ACTIVITY OF COMPOUNDS ISOLATED FROM Conchocarpus heterophyllus. The phytochemical investigation of trypanocidal extracts from leaves and stems of Conchocarpus heterophyllus (A. St.-Hil.) Kallunki & Pirani (Rutaceae) afforded new pyranoflavones along with the known compounds flavone, 7-methoxyflavone, 5-hydroxyflavone, haplotusine, 1-methyl-2-phenyl-4-quino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
(16 reference statements)
1
13
0
2
Order By: Relevance
“…Similar studies involving the trypanocidal activity of Meliaceae and Rutaceae species have been reported by our group (Mafezoli et al, 2000;Vieira et al, 2001;Ambrozin et al, 2004Ambrozin et al, , 2005aAmbrozin et al, , 2008 showing that these plants can be considered a promising source of active compounds against trypomastigote forms of T. cruzi. Thus, the significant results obtained from the extracts of C. fruticosa are consistent with those previously reported for this family.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar studies involving the trypanocidal activity of Meliaceae and Rutaceae species have been reported by our group (Mafezoli et al, 2000;Vieira et al, 2001;Ambrozin et al, 2004Ambrozin et al, , 2005aAmbrozin et al, , 2008 showing that these plants can be considered a promising source of active compounds against trypomastigote forms of T. cruzi. Thus, the significant results obtained from the extracts of C. fruticosa are consistent with those previously reported for this family.…”
Section: Resultssupporting
confidence: 87%
“…The bioassays were carried out according to the procedures described by Ambrozin et al (2008). The activity of crude extracts was evaluated in triplicate at 4 mg/mL and pure substances at 250, 100, and 50 µg/ mL.…”
Section: Bioassaymentioning
confidence: 99%
“…It is caused by parasitic protozoan Trypanosoma cruzi and represents one of the most serious endemics diseases in Brazil. Of particular public health concern, it affects 16-18 million individuals in the Americas, with 100 million under risk of contamination (Ambrozin et al 2008). The parasite can be transmitted to humans through the faces and urine of vectors (triatomines), infection with T. cruzi through the transfusion of blood products and organ transplants from the infected donors.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Literature reports of phytochemical studies with Conchocarpus species have shown the presence of alkaloids, flavonoids and coumarins in addition to anti-Trypanosome cruzy activity. [6][7][8][9] In the present paper, we used stems from Conchocarpus cyrtanthus commonly known as "Orelha de cabra" to describe the isolation and characterization of two new diterpenes 16-hydroxylarixol (1), 16-hydroxy-7-labden-6-one (2) besides twelve known compounds: three coumarins seselin (3), xantoxiletin (4) in de Oliveira, L. S. S. et al Rev. Virtual Quim.…”
Section: Introductionmentioning
confidence: 99%
“…|Vol 8| |No. 1| |87-96| 89 mixture, luvangetin (5), the alkaloid dictamin (6), six steroids -sitosterol (7), stigmasterol (8), campesterol (9) in mixture, 7-hydroxy--sitosterol (10), 7-hydroxy-stigmasterol (11) 7-hydroxy-campesterol (12) in mixture, three diterpenes manool (13), 16-hydroxymanoiloxide (14) 16-hydroxy-13-epimanoyloxide (15), and the lignan siringaresinol (16).…”
Section: Introductionmentioning
confidence: 99%